Pathology Content Selection in a Medical Imaging Programme in New Zealand: An Exploration of Lecturers' Beliefs - Yang, Lixin (Auckland University of Technology, 2025)
This study investigated how five medical imaging lecturers at Unitec select pathology teaching content. There is no agreed-upon curriculum or standard in New Zealand (NZ) for the amount and/or range of pathology content that should be taught in Medical Imaging (MI) programmes, so lecturers tend to select what to include based on their individual experiences and beliefs. The large amount of pathology content that could be taught, and the reluctance of some MI students to engage with that content, makes it challenging to decide what to include in MI programmes. While there is a great deal of literature on pathology education in medicine, there is a lack of research about what pathology knowledge and skills could be taught to medical imaging students in New Zealand from the perspective of lecturers who are familiar with medical imaging profession and its education. Informed by an interpretivism paradigm, this qualitative study used semi-structured interviews to investigate medical imaging lecturers beliefs about pathology content selection. The analysis of the data utilises a conceptual framework developed from a literature review, highlighting the broader aims of education, the importance of teaching content, and what counts as subject knowledge in curriculum development. The main finding of the study is that lecturers experience great tension in pathology content selection because their decisions are influenced by several different critical considerations. As they make their decisions some of the broader aims of education sometimes collide with each other. Lecturers generally believe that adequate pathology knowledge should be covered in MI courses, including underlying pathologic changes for essential clinical presentations and imaging features. However, the lack of pathology content requirements associated with a lack of advanced practice of medical imaging technologists, as well as the reluctance of students to engage with learning they do not see as relevant, presents significant challenges. It is hoped that the findings of this study will produce more insight into the challenges faced by both lecturers and medical imaging students in pathology teaching and learning. It is also hoped that the study will promote further discussion among medical imaging educators, practitioners, and people from regulation bodies about what pathology knowledge and skills should be taught to medical imaging students.